Analisis Pengaruh Kemudahan terhadap Tingkat Efektivitas Penggunaan Mesin Cetak Pelet Pakan Ternak - Salsabila Diba Cahyani; Nur Aziezah; Hikmah Rahmah; Faldiena Marcelita; Inna Novianty (Universitas Katolik Widya Karya Malang, 2024)
The pellet molding machine has high efficiency to make it easier to process animal feed pellets. The pellet processing process requires a series of activities such as grinding, mixing, pelleting and drying. Therefore, research was carried out to identify the effect of convenience on the level of effectiveness of using an animal feed pellet printing machine. The method used in this research is a quantitative method by distributing questionnaires via the Google Form platform. Validity tests, reliability tests and simple regression analysis are used to analyze the data obtained from filling out the questionnaire